Analisa External Flow Pada Mobil Tesla Model S Saat Melaju di Tikungan - Fadil Djanuarno, Alief; Wijaya Kusuma, I Gusti Bagus; Suarnadwipa, N.; Suarnadwipa, N. (Teknik Desain Mekanika, 2021)
Abstract Aerodynamic forces play a major role in causing accidents in vehicles. This occurs when the car is traveling at high speed and receives aerodynamic forces by the wind both crosswind and from the rear (tailwind). Crosswind will cause the car to slip which continues with slippage, and ends up rolling over. Meanwhile, the tailwind will cause the car to slide freely even though it does not slip directly. This research was conducted by analyzing the CFD (Computational Fluid Dynamic) application to analyze external flow and find out the value of the pressure gradient that occurs in the 3D model of the Tesla Model S car and it is simulated as when moving through a bend, such as driving, driving with a slip, experiencing a slip as well as skid, and turn. The higher the speed of the car when turning, the shift in the center of gravity of the car will be greater. Starting from going without a slip at a speed of 80 km/h and 140 km/h the car has no center of gravity shift, traveling with a slip at a speed of 80 km/h and 140 km/h the car has a shift of center of gravity of 5.33896 mm and 50.0372 mm , and traveling slip and skid at speeds of 80 km/h and 140 km/h the car had a shift in the center of gravity of 15.2613 mm and 221.84 mm. Keywords: Aerodynamics, Computational Fluid Dynamics, Slip, Skid, Vehicle Dynamics, Center Of Gravity